The ‘Architectural’ Projects for the Church of St. Ignatius by Andrea Pozzo (diségno, 2019)
Andrea Pozzo –a painter, scenographer, and master of perspective– should always be fully recognized as an architect in the cultural panorama of the baroque period. This artist from Trento created his works in the church of St. Ignatius in Rome between 1685 and 1694, where he depicted St. Ignatius protector of afflicted people in the apse semi-dome (1685–1688), the Glory of St. Ignatius on the vault of the central nave (1687–1693), and the false dome (1685) to replace the one that had been designed but never built. For the works mentioned, Pozzo aimed to ‘construct’ a building that, while being illusory, did not exist in reality, lives amid the space of the physical architecture of the church. The documentation, which evidences the various sequential phases of creation, was studied to recompose the design path he followed [Salviucci Insolera 2015]. The goal of this paper is therefore to define and verify the design process that Pozzo used to create these works. From the committee’s request to the drafting of the first sketches, to the drawings that aim to represent the building as it is and as it appears. Everything can be found in his work and is supported by graphical and textual documents for the designs of the dome and vault. Finally, an analysis of the relationships between his three designs for the church of St. Ignatius poses further questions regarding the existence of an unifying intent formulated by Pozzo.
Keywords: Andrea Pozzo; church of St. Ignazius; architectural perspectives; project drawing; Perspectiva pictorum et architectorum